Does the Continuous Performance Test Predict ADHD Symptoms Severity and ADHD Presentation in Adults?. Issue 6 (April 2020) - Baggio, Stéphanie; Hasler, Roland; Giacomini, Véronique; El-Masri, Hiba; Weibel, Sébastien; Perroud, Nader; Deiber, Marie-Pierre
Objective: Our study aimed to provide empirical evidence on the usefulness of one of the most popular neuropsychological tests, the Continuous Performance Test (CPT), as a marker of ADHD severity and presentations among adults.Method: ADHD participants were recruited in a specialized center for the diagnosis and treatment of adults suffering from ADHD ( n = 201). Measures included the CPT3™ and ADHD symptoms using a clinical interview and self-reported measures.Results: Only 51.7% of the participants were classified as likely to have a disorder characterized by attention deficit, such as ADHD, by the CPT. The relationships between CPT variables and ADHD symptoms were small. The classification error was 80.3% for the inattentive presentation and 22.5% for the hyperactive presentation when using the CPT to identify ADHD presentations.Conclusion: There was no evidence of the clinical utility of the CPT to assess or monitor ADHD in adult populations diagnosed and treated for ADHD.